2009
DOI: 10.1073/pnas.0901515106
|View full text |Cite
|
Sign up to set email alerts
|

Identification of intracellular carriers for the endocannabinoid anandamide

Abstract: The endocannabinoid anandamide (arachidonoyl ethanolamide, AEA) is an uncharged neuromodulatory lipid that, similar to many neurotransmitters, is inactivated through its cellular uptake and subsequent catabolism. AEA is hydrolyzed by fatty acid amide hydrolase (FAAH), an enzyme localized on the endoplasmic reticulum. In contrast to most neuromodulators, the hydrophilic cytosol poses a diffusional barrier for the efficient delivery of AEA to its site of catabolism. Therefore, AEA likely traverses the cytosol wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
332
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(354 citation statements)
references
References 64 publications
5
332
1
3
Order By: Relevance
“…The decreased responsiveness to OEA in L-Fabp Ϫ / Ϫ mice may also refl ect alterations in intracellular traffi cking. Recent studies showed that overexpression of FABP7 and FABP5 increased uptake and hydrolysis of AEA in Cos7 cells, suggesting that FABPs may facilitate the intracellular traffi cking of this hydrophobic ligand ( 13 ). It is tempting to speculate that L-Fabp may play a role in facilitating intracellular movement of either fatty acids for FAE synthesis Supplemental Material can be found at:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decreased responsiveness to OEA in L-Fabp Ϫ / Ϫ mice may also refl ect alterations in intracellular traffi cking. Recent studies showed that overexpression of FABP7 and FABP5 increased uptake and hydrolysis of AEA in Cos7 cells, suggesting that FABPs may facilitate the intracellular traffi cking of this hydrophobic ligand ( 13 ). It is tempting to speculate that L-Fabp may play a role in facilitating intracellular movement of either fatty acids for FAE synthesis Supplemental Material can be found at:…”
Section: Discussionmentioning
confidence: 99%
“…1A ) after 5 months of age, with decreased fat mass as determined by both MRI ( Fig. 1B ) and DEXA (data not shown) analysis at carrier proteins, including fatty acid binding proteins (FABP), in the metabolic compartmentalization of these mediators ( 13,14 ). L-Fabp is an abundant cytosolic FABP expressed in hepatocytes and in enterocytes of the proximal small intestine.…”
Section: Aged Female L-fabpmentioning
confidence: 99%
“…Considering the fact that AEA does not bind appreciably to borosilicate glass, the use of coverslips seems particularly indicated to perform export experiments. More importantly, the new procedure can be also extended to the subcellular level ( 49,50 ) by taking advantage of b-AEA as a nonradioactive probe to look at anandamide traffi cking within intact cells by light, fl uorescence, and electron microscopy techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Although this model supports the existence of a plasma membrane-localized AEAbinding protein, it cannot explain why uptake inhibitors also affect AEA efflux. Right after the identification of several cytosolic AEA "chaperone" proteins, such as FABP5, FABP7, Hsp70, albumin, and the more controversial FLAT (274,415,637,773), a revised version of the simple diffusion model was proposed. According to this model, the passive diffusion process of AEA across the membrane is followed by intracellulaer carrier-mediated transport to effector proteins, catabolic enzymes, and sequestration sites (268,270).…”
Section: Endocannabinoid Biosynthesis and Degradationmentioning
confidence: 99%